Hair-cutting as a form of religious discrimination: evaluating the school code of conduct in the case of Nazareth Baptist Church learners - Mlungisi Vusumuzi, Hlabisa (British Journal of religious education, 2026)
Despite numerous reform measures by the state to promote justice and equality, South Africa finds itself far from its main constitutional objective of unity in diversity. The country is still faced with many social injustices and intolerances, and religious discrimination is no different. There have been several court cases heard in South Africa that point to religious intolerance in schools. This paper illustrates systemic religious discrimination against learners of the Nazareth Baptist Church encoded in ten schools’ codes of conduct. It offers a postcolonial critique of these codes in a postcolonial/post-Apartheid South Africa. Using a case study approach, which follows an interpretivist document analysis, this research analyses school codes of conduct in northern KwaZulu Natal schools. The schools were purposefully selected based on the criteria that there are three major religions existing in that area: Christianity, Nazareth Baptist Church and African Traditional Religions. The study found that codes of conduct marginalise learners from the Nazareth Baptist Church by forcing them to cut their hair; therefore, misrecognising their religion. It explored how cut-hair is a colonial marker for civility and cleanliness. There is a need for School Governing Bodies to revisit codes of conduct to be inclusive of other religions.